1977
DOI: 10.1002/cpt1977225part1528
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine, a new antihypertensive with rapid action

Abstract: Oral (17 cases) or sublingual (9 cases) administration of nifedipine (10 mg), a new coronary dilator, induced a prompt and large pressure reduction in patients with severe primary hypertension. Pressure started to fall within 20 and 5 min after oral and sublingual administration, respectively, and reached the lowest levels in the next 10 min. Maximal mean arterial pressure reduction averaged 36 mm Hg; 120 min after the drug, mean arterial pressure was diminished by 19.5% of control. The hypotension was mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(50 citation statements)
references
References 4 publications
4
46
0
Order By: Relevance
“…Esper et al (1975) and Linke (1975) (Muracakami et al, 1972;Guazzi et al, 1977;Simonsen & Nitter-Hauge 1978); and it is possible that this increase may counteract their hypotensive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Esper et al (1975) and Linke (1975) (Muracakami et al, 1972;Guazzi et al, 1977;Simonsen & Nitter-Hauge 1978); and it is possible that this increase may counteract their hypotensive effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that this drug exerts a prompt and marked hypotensive effect when administered to hypertensive patients (Murakami et al, 1972;Aoki et al, 1976;Guazzi et al 1977;Pedersen and Mikkelsen 1978;Imai et al 1980) and the drug has been accepted as a critical therapeutic for several forms of hypertension (Guazzi et al 1983;Massie et al 1984; Muhller et …”
mentioning
confidence: 99%
“…The haemodynamic profile of amlodipine is also in keeping with other reports of dihydropyridine calcium channel blocking agents in clinical practice. Nifedipine has been shown to reduce peripheral vascular resistance and increase heart rate and cardiac output (Guazzi et al, 1977;Murakami et al, 1972;Simonsen & Nitter-Hauge, 1978). Similar profiles for nicardipine have been shown by Rousseau et al (1984b), Visser et al (1985) and Lambert et al (1985) and for nisoldipine by Vogt et al (1980Vogt et al ( , 1983.…”
Section: Discussionmentioning
confidence: 99%